2019
DOI: 10.1101/645275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of IL-33 and IL-5 Family Mediated Activation of Human Eosinophils

Abstract: 23 24 25 2 26 ABSTRACT 27 28 Eosinophils are the prominent inflammatory cell involved in allergic asthma, atopic dermatitis, 29 eosinophilic esophagitis, and hypereosinophilic syndrome and are found in high numbers in local tissue 30 and/or circulating blood of affected patients. There is recent interest in a family of alarmins, including 31 TSLP, IL-25 and IL-33, that are epithelial-derived and released upon stimulation of epithelial cells. Several 32 genome wide association studies have found SNPs in genes e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 40 publications
2
16
1
1
Order By: Relevance
“…IL-33 is an epithelial cell-derived molecule, although it can also be made by macrophages. Recent experiments have suggested that IL-33 can be as potent as IL-5 and CCL11 in controlling eosinophil migration (30,31). We found increased IL-33 production in RV-infected HDM allergic mice, and the previously mentioned study demonstrated enhanced IL-33 expression in lung epithelial cells in cockroach allergen allergic mice and that blocking IL-33 partially reduced eosinophilia driven by RV (15), supporting a role for this cytokine.…”
Section: Discussionsupporting
confidence: 83%
“…IL-33 is an epithelial cell-derived molecule, although it can also be made by macrophages. Recent experiments have suggested that IL-33 can be as potent as IL-5 and CCL11 in controlling eosinophil migration (30,31). We found increased IL-33 production in RV-infected HDM allergic mice, and the previously mentioned study demonstrated enhanced IL-33 expression in lung epithelial cells in cockroach allergen allergic mice and that blocking IL-33 partially reduced eosinophilia driven by RV (15), supporting a role for this cytokine.…”
Section: Discussionsupporting
confidence: 83%
“…2a, b). In addition to acting through ILC2 and Th2 cells, IL-33 also acts directly on eosinophils, inducing their activation and expansion [63,64]. Therefore, its absence in IL-33 -/mice can explain the small number of eosinophils in the in ammatory in ltrates in the sixth week of infection (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is understandable that the absence of IL-33 in IL-33 −/− mice at the early stage of the patent infection might have left them inactivated, leading to impaired type 2 immunity (58) as seen in the present study. In addition to acting through ILC2 and Th2 cells, IL-33 also acts directly on eosinophils, inducing their expansion and activation (59,60). Therefore, its absence in IL-33 −/− mice can explain the small number of eosinophils in the in ammatory in ltrates in the sixth week of infection (61).…”
Section: Discussionmentioning
confidence: 99%